Hyaluronan for knee osteoarthritis: an updated meta-analysis of trials with low risk of bias. Issue 1 (14th May 2015) - Richette, Pascal; Chevalier, Xavier; Ea, Hang Korng; Eymard, Florent; Henrotin, Yves; Ornetti, Paul; Sellam, Jérémie; Cucherat, Michel; Marty, Marc
Abstract : Background: The effectiveness of intra-articular hyaluronic acid (IAHA) injection for knee osteoarthritis (KOA) is debated. Objectives: To evaluate the effect of IAHA for patients with KOA by analysing data from trials of IAHA versus placebo with low risk of bias, to provide the highest level of evidence. Methods: A systematic review and meta-analysis was conducted. Randomised controlled trials (RCTs) with a low risk of bias (adequate randomisation and concealment and double-blind design) that investigated IAHA versus placebo (saline solution) injection were eligible. The primary efficacy measure was pain intensity and secondary outcome function at 3 months. The treatment effect was summarised with the standardised mean difference (SMD) calculated from differences in means of pain and function measures between treatment and control groups at 3 months. Trials were pooled by a random-effects model with DerSimonian and Laird weights. Statistical heterogeneity was explored by a visual exploration of forest plots and the I 2 statistic. Results: A total of eight RCTs (2 199 randomised patients) met our inclusion criteria. IAHA significantly reduced the pain intensity (SMD=−0.21, 95% CI (95% CI) −0.32 to −0.10) and improved function (SMD=−0.12, 95% CI −0.22 to −0.02). Trials showed no heterogeneity. Conclusions: This meta-analysis of high-quality trials of IAHA versus placebo shows that IAHA provides a moderate but real benefit for patients with KOA.